How "American" is Barack Obama? The Role of National Identity in a Historic Bid for the White House. Issue 1 (7th November 2012) - Devos, Thierry; Ma, Debbie S.
<x xml:space="preserve">Abstract</x> Against the backdrop of the 2008 presidential election, we examined the extent to which the American identity was implicitly and explicitly associated with Barack Obama compared to Tony Blair (Study 1), Hillary Clinton (Study 2), and John McCain (Studies 3 and 4). When conscious control was relatively limited and targets were categorized based on race, the American identity was less strongly associated with Obama than with the other candidates. This effect was stronger than when the candidates were categorized based on their personal identity (Studies 1–4), gender (Study 2), political affiliation (Study 3), or age (Study 4). In addition, the extent to which candidates were differentiated in terms of implicit and explicit associations with the American identity predicted the relative willingness to actively support them.